Comparison of Methods for Individual Killing of Broiler Chickens: A Matter of Animal Welfare and On-Farm Feasibility - Watteyn, Anneleen; Garmyn, An; Ampe, Bart; Jacobs, Leonie; Moons, Christel P. H.; Tuyttens, Frank A. M. (Frontiers in Animal Science, 2022)
The humane killing of individual broiler chickens on farm requires a minimum of suffering. In this regard, rapid and irreversible loss of consciousness are important determinants. This can be verified by cerebral and spinal reflexes. Also on-farm feasibility determines whether or not producers will apply the method. The aim of the study was to compare the effectiveness and animal welfare impact of two different methods for killing individual broilers of varying ages (2-4-6 weeks): manual cervical dislocation (CD) and captive bolt (CB). The evaluation of CD and CB was based on effectiveness and on time to onset (convulsions) or cessation (pain response, pupillary light reflex, convulsions, heartbeat) of non-invasive indicators. In addition, a pilot study was conducted on-farm to assess the feasibility of two alternative methods, CB and nitrogen gasification (N2), and to survey farmers' opinions on them. The onset of convulsions was almost immediate for both methods in the first study. No differences between CD and CB were observed for the cessation of pain response for chickens at age of 2 (5.0 and 7.5 s, respectively) and 6 weeks (14.0 and 14.1 s, respectively). However, at 4 weeks a longer pain response was measured after CD (11.3 s) than after CB (4.7 s). For the three age categories, the pupillary light reflex disappeared later after CD (54.9 - 80.7 s) compared to CB (8.3 - 13.7 s). The same was observed for cessation of convulsions in 2- and 6-week-old chickens (185.3 and 172.0 s for CD and 79.0 and 82.9 s for CB). This suggests that brain death occurred faster after CB compared to CD. No difference between the methods was found for the cessation of the heartbeat. After pilot study, the producers preferred N2 over CB in terms of animal-friendliness, time-efficiency, ease of use, and effectiveness. However, both methods were found rather expensive and required some experience. CB and N2 are good killing alternatives to CD due to rapid and irreversible insensibility. However, more information and support for chicken producers will be needed for these to become routine killing methods.